Promoting Students’ Autonomy in Written Communication Through Scaffolding Strategy - Vike Aprilianin Marwintaria Saputri; Ine Yudhawati; iin Avitasari; Sidartha Adi Gautama; Wistina Seneru (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2023)
The purposes of this study is to investigate the difference of the students’ written communication autonomy after the implementation of scaffolding strategy. The sample is twenty students of the first-year semester of the undergraduate students of the Buddhist Communication Science Department in Jinarakkhita Buddhist College of Lampung. This research is quantitative by using one group pre-test posttest design. The instruments are writing test, questionnaire and interview. The result of data analysis shows that scaffolding strategy can further promote the students’ autonomy in written communication significantly. The result of the questionnaire shows that the students give the positive response towards applying scaffolding strategy in writing class. The conclusion of this present study, after the students are given scaffolding strategy, along with the improvement in written communication ability, the students’ autonomy in writing improves significantly.